2017
DOI: 10.18433/j30d2v
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Emulsion, More Than Reversing Bupivacaine Cardiotoxicity: Potential Organ Protection

Abstract: Efforts to develop a treatment for bupivacaine cardiotoxicity led to the discovery that Intralipid, a popular brand of intravenous lipid emulsion, could be used not only as an effective treatment for anesthetic-induced cardiac arrest, but also as a means of reversing many other toxicities. Contradictory data exist regarding the mechanism of action of lipid emulsion, a combination of fatty acids traditionally used in parenteral nutrition. Some researchers attribute the effects to lipophilicity and the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In this study, we have developed a new drug delivery by diluting PTX into commercial 20% lipid emulsion prior to use. Lipid emulsion is widely used as a parenteral emulsion in the market, and is safe and well tolerated even in low-birth-weight infants and children for nutritional support (Motayagheni et al, 2017). PEG400 is a biocompatible polymer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have developed a new drug delivery by diluting PTX into commercial 20% lipid emulsion prior to use. Lipid emulsion is widely used as a parenteral emulsion in the market, and is safe and well tolerated even in low-birth-weight infants and children for nutritional support (Motayagheni et al, 2017). PEG400 is a biocompatible polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Even multiple drugs were assessed [1,20], but none proved to be bene cial in large scale studies for myocardial protection. Now, intralipid may play a novel and potential role in cardioprotection with bright prospect [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Improving myocardial energy metabolism can reduce myocardial I/R injury [2]. Since the myocardium relies mainly on fatty acid oxidation (FAO) instead of glycometabolism to provide energy, some experimental studies indicated that supplementing the exogenous FAO substrate can increase the supply of myocardial ATP and thus exert cardioprotection [3][4][5][6][7]. However, preischemic exposure of fatty acids will lead to insu cient FAO during the period of ischemia and cause cardiotoxicity injury subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…Even multiple drugs were assessed [1,20], but none proved to be beneficial in large scale studies for myocardial protection. Now, intralipid may play a novel and potential role in cardioprotection with bright prospect [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Improving myocardial energy metabolism can reduce myocardial I/R injury [2]. Since the myocardium relies mainly on fatty acid oxidation (FAO) instead of glycometabolism to provide energy, some experimental studies indicated that supplementing the exogenous FAO substrate can increase the supply of myocardial ATP and thus exert cardioprotection [3][4][5][6][7]. However, preischemic exposure of fatty acids will lead to insufficient FAO during the period of ischemia and cause cardiotoxicity injury subsequently.…”
Section: Introductionmentioning
confidence: 99%